Respuestas
Respuesta dada por:
2
respuesta 1
![\frac{y}{3} + \frac{y \times 2z}{3} - \frac{11}{3} = 0 \\ \\ \frac{x}{3} + \frac{2yz}{3} - \frac{11}{3} = 0 \\ \\ x - 2yz - 11 = 0 \\ \\ x = - 2yz + 11 \\ \frac{y}{3} + \frac{y \times 2z}{3} - \frac{11}{3} = 0 \\ \\ \frac{x}{3} + \frac{2yz}{3} - \frac{11}{3} = 0 \\ \\ x - 2yz - 11 = 0 \\ \\ x = - 2yz + 11 \\](https://tex.z-dn.net/?f=+%5Cfrac%7By%7D%7B3%7D+%2B+%5Cfrac%7By+%5Ctimes+2z%7D%7B3%7D+-+%5Cfrac%7B11%7D%7B3%7D+%3D+0+%5C%5C+%5C%5C+%5Cfrac%7Bx%7D%7B3%7D+%2B+%5Cfrac%7B2yz%7D%7B3%7D+-+%5Cfrac%7B11%7D%7B3%7D+%3D+0+%5C%5C+%5C%5C+x+-+2yz+-+11+%3D+0+%5C%5C+%5C%5C+x+%3D+-+2yz+%2B+11+%5C%5C+)
respuesta 2
respuesta 2
JonatanDavid14x:
Tenia algunos errores, actualiza para que te aparesca bien la solución.
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años